Evolution of single carbon and glass fibrous tow cross-sections in dry and lubricated states during compaction perpendicular to the fibers. (1st September 2018) - Dharmalingam, A. Sakkalatty; Hemmer, J.; Lectez, A.-S.; Binetruy, C.; Comas-Cardona, S.
Abstract: Fibrous fabrics are used in a variety of applications, among them, for structural composites. Most fabrics are efficiently manufactured from tows or yarns. During textile manufacturing or during fiber reinforced composites manufacturing, the fabrics and tows undergo several movements and deformations. Although there have been several attempts by different authors to model micro structural mechanical behavior of fabrics, they often suffer from unknown geometric dimensions at various loads or unknown materials' mechanical parameters. This paper presents a method for measuring and comparing tows (or yarns) geometrical evolution during compaction perpendicular to the fibers. The tows are compacted and dimensions are continuously measured using confocal chromatograph. Fabrics and tows of the study are composed of glass or carbon fibers, in dry or lubricated states. Volume, compacity evolutions and Poisson's ratio are extracted for a wide range of compaction levels. Tables of material characteristics and experimental data are also provided for a further use or analysis.